The impact of the COVID-19 pandemic on the career choice of medicine: A cross-sectional study amongst pre-medical students in Pakistan. (September 2022) - Saleh, Raisa; Martins, Russell Seth; Saad, Muhammad; Fatimi, Asad Saulat; Kumar, Gaurav; Abbas, Manzar; Akbar, Inaara; Jehanzeb, Hamzah; Ladak, Shamila; Kaleem, Shamama; Nadeem, Sarah
Abstract: Background: The COVID-19 pandemic has significantly affected the lives of healthcare workers due to the frontline nature of their work. Their hard work and sacrifice have forged new perceptions of healthcare workers. These changes may potentially influence students' interest in medicine. This study explores how the COVID-19 pandemic has affected premedical students' decisions to pursue medicine as a career. Methods: A cross-sectional study using a self-designed online questionnaire was carried out amongst pre-medical students across Pakistan. Results: A total of 1695 students from 93 public and private schools filled in the survey. After the onset of the COVID-19 pandemic, significantly more pre-medical students want to pursue medicine (60.7%–62.9%) and less are unsure (20.2%–17%). Students are significantly more likely to be motivated to pursue medicine due to altruistic benefits to society (57% vs. 62.7%) and be deterred by the risk of contracting infections on duty (10%–14.6%). There is a minor but significant increase in the popularity of internal medicine (17.1%–18.9%), public health (4.1% vs. 5.7%), emergency medicine (3.8% vs. 5.7%), pediatrics (3.8% vs. 4.7%), and radiology (2.1% vs. 2.9%). Most pre-medical students felt that doctors routinely undergo physical and emotional turmoil (84%). Conclusions: Although awareness of hardships faced by medical professionals has increased, motivation to pursue medicine has grown. Through understanding trends in the motivations of students to pursue medicine, medical schools can accommodate the expectations of incoming students and reach out to potential applicants. Highlights: More pre-medical students want to pursue medicine since the onset of the pandemic. The major motivation to pursue medicine remains altruistic. Since the pandemic, students are more likely to be deterred by occupational risks. Some specialties have become more popular choices since the pandemic. These include pediatrics, public health, and internal medicine.